Survival strategy of the endangered tree Acer catalpifolium Rehd., based on 13C fractionation. Issue 16 (5th August 2020) - Song, Wenchen; Liu, Yanhong
Abstract: We conducted a field investigation and evaluation of 13 C natural abundance to determine the growth habit and propagation strategy of Acer catalpifolium Rehd., a tree species native to China that is highly endangered. The results showed that A .  catalpifolium is a K‐selected strategist and pioneer species. Its narrow ecological range limits its geographical distribution, and poor fecundity limits its population size. The analysis of 13 C natural abundance showed that A .  catalpifolium does not use organic matter for reproduction when its stand volume is less than 1.08 × 10 6  cm 3 or it is less than 18.6 m tall, but it does use this strategy when it has a sufficient 1.08 × 10 6  cm 3 stand volume or more or is taller than 18.6 m. If environmental conditions are not conducive (e.g., severe human disturbance, cliff edges, or fierce interspecific competition) to the continued growth of the tree, A .  catalpifolium may allocate organic matter for reproduction. Human disturbance seems to promote the population expansion of A .  catalpifolium . We provide our suggestions for the promotion and protection of A .  catalpifolium as a species. Abstract : This study involved a field investigation and evaluation of 13 C natural abundance to determine the growth habit and propagation strategy of Acer catalpifolium Rehd., a tree species native to China that is highly endangered. Its narrow ecological range limits its geographical distribution, and poor fecundity limits its population size. The analysis of 13 C natural abundance showed that A .  catalpifolium allocates organic matter for reproduction only when it has accumulated sufficient biomass and height or when environmental conditions are not conducive to continued growth.